Sin and Sanction in Israel and Mesopotamia. A Comparative Study - van der Toorn, Karel (1985)
ersch. 1986; Appendix, p. 117-154: The šigû Prayers. Place and Purpose of the Dingiršadibba Prayers. Texts; pl. 1-9: copies of K. 254 + 3369, 2425, 2581, 2583 + 10409, 3514, 39,37, 9252, 9453, DT 119+ 152, 79-7-8,71; BM 72012. Wiederholung von 47:1753.